Expression and purification of full-length Alanyl-tRNA-synthetase from Thermus thermophilus HB27 - Rybak, M.Yu.; Priss, A.E.; Gudzera, O.I.; Kovalchuk, A.O.; Kryklyvyi, I.A.; Tukalo, M.A. (Вiopolymers and Cell, 2018)
Aim. To gain insight into structural and functional properties of alanyl-tRNA,synthetase (AlaRS), we genetically engineered constructs for expression and purification of full-length AlaRS and checked its activity in aminoacylation assays. Methods. The genomic DNA for the AlaS gene from the T. thermophilus (HB 27 strain) was amplified by PCR and cloned into vectors with and without a histidine tag. To optimize conditions for the protein expression in E. coli and to develop efficient purification procedure, the molecular biology techniques were applied. AlaRS was purified by affinity and size-exclusion chromatography. The molecular weight of enzyme was determined by gel filtration. Results. The expression and purification conditions for recombinant AlaRS were optimized. Approximately 1.5 mg of the pure active recombinant enzyme can be obtained from 1 L of bacterial culture. AlaRS from T. thermophilus is a dimer in solution with an experimental MW of 204 kDa. Conclusions. The purified recombinant enzyme will be used for further studies on the functional kinetics and structure of the crystal complex with tRNA.